1997
DOI: 10.1093/clinchem/43.7.1223
|View full text |Cite
|
Sign up to set email alerts
|

Plasma protein abnormalities in nephrotic syndrome: effect on plasma colloid osmotic pressure and viscosity

Abstract: The concentrations of 25 plasma proteins were measured in 22 patients with membranous nephropathy. For some large proteins, the plasma concentrations were increased; there were also large proteins with low plasma concentrations, but small or medium-sized proteins showed uniformly lower plasma concentration than the controls. Plasma colloid osmotic pressure (π) and viscosity (η) were not interrelated but showed positive and significant correlations with plasma concentrations of small and medium-sized proteins (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…21 Joven J et al, had also reported similar finding of mean cholesterol 10.83±4.96, HDLc=1.43±0.32, TG= 3.98±1.12 respectively. 22 Francisco AT et al, recognize the strong inverse relationships between proteinuria and serum albumin also between serum albumin and plasma total cholesterol. Such inverse relationships with TC and TG with the serum albumin were also seen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…21 Joven J et al, had also reported similar finding of mean cholesterol 10.83±4.96, HDLc=1.43±0.32, TG= 3.98±1.12 respectively. 22 Francisco AT et al, recognize the strong inverse relationships between proteinuria and serum albumin also between serum albumin and plasma total cholesterol. Such inverse relationships with TC and TG with the serum albumin were also seen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with nephrotic syndrome (hypoalbuminaemia, <3 g/100 ml; proteinuria, >3 g/day; and oedema formation) also exhibit hypercholesterolaemia, hyperlipidaemia and low serum albumin concentration. [70] In patients with nephrotic syndrome, the plasma concentration of α2-macroglobulin was also higher (by 197%) than that in control subjects. [70] Although hepatic CYP changes in patients with nephrotic syndrome have not been reported, NARs could serve as an animal model for the patients.…”
Section: Discussionmentioning
confidence: 95%
“…[70] In patients with nephrotic syndrome, the plasma concentration of α2-macroglobulin was also higher (by 197%) than that in control subjects. [70] Although hepatic CYP changes in patients with nephrotic syndrome have not been reported, NARs could serve as an animal model for the patients. In NARs and patients with nephrotic syndrome, effects of plasma albumin binding in circulating blood in the diuretic effect of furosemide have been reported.…”
Section: Discussionmentioning
confidence: 95%
“…Kaneko [22] stated that increases solely in the β-globulin fraction are not frequent and may be typical for active hepatitis. Chronic persistent liver disease, liver cirrhosis, as well as nephrotic syndrome may be associated with elevations in the β-region due to the increase of the concentrations of β 2 -microglobulin in these conditions [256]. High β-globulin concentrations may be associated also with hypercholesterolemia, which is caused by increased concentrations of β-lipoproteins in this fraction [257].…”
Section: Changes In the Globulin Fractionsmentioning
confidence: 99%